Pengaruh E-Lib UIN SMDD Bukittinggi terhadap Penelusuran Informasi Mahasiswa Tahun Masuk 2020 Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi - Indriani, Afifah; Nelisa, Malta (YASIN, 2024)
This study aims to determine how: (1) a significant relationship between the e-lib UIN SMDD Bukittinggi on information searches of students in 2020, Faculty of Economics and Islamic Business, Sjech M. Djamil Djambek Bukittinggi State Islamic University; (2) a significant relationship between information searches on the e-lib UIN SMDD Bukittinggi on students in 2020, Faculty of Economics and Islamic Business, Sjech M. Djamil Djambek Bukittinggi State Islamic University. Djamil Djambek Bukittinggi; (3) the influence of the e-lib UIN SMDD Bukittinggi on the information search of students in 2020, Faculty of Economics and Islamic Business, State Islamic University Sjech M. Djamil Djambek Bukittinggi. The research uses descriptive methods with quantitative research types. This study consists of two variables, namely the e-library variable (X) and the information search variable (Y). The population of this study were all students of the Faculty of Economics and Islamic Business in 2020 as many as 1,137 people. The sample was taken as many as 92 using the Slovin formula. The technique used is simple random sampling technique. Data were collected through questionnaires with data analysis techniques. Based on the research results, it is known that the coefficient of determination test of the e-library variable (X) gives an influence on information search (Y) of 86.1% while the remaining 13.9% is influenced by other factors not examined in this study. While based on the T-test, the alternative hypothesis (Ha) is accepted while the null hypothesis (H0) is rejected, thus showing that e-library has a positive and significant effect on information search.